(untitled) (Bangladesh Journal of Medical Science, 2012)
Introduction: Hs-CRP is a nonspecific marker of the inflammatory response has been associated with development of type 2 diabetes mellitus. Cardiovascular disease is a major consequence of diabetes. DM confers a 2-4 fold rise in cardiovascular risk compared with general population. One of the many modifiable risk factors for both cardiovascular disease and diabetes is diet. Fiber is an important dietary factor that may modify the risk of both diseases. Material & methods: The current study is an attempt to explore the association of dietary fiber on inflammatory marker, hs-CRP in type2 diabetic subjects. Total 80 diabetic subjects were included in this study of which 40 were taking more dietary fiber and 40 were taking relatively low dietary fiber. Serum hs-CRP was measured by chemiluminescent immunometric assay (DPC Biermann Gmbh., Germany). Nutrient information was calculated using a pretested food recall questionnaire prepared by nutritionists for usual Bangladeshi food articles. Results: Hs-CRP was significantly higher in subjects taking low dietary fiber. There was significant negative correlation between CRP of subjects taking high and low intake of dietary fiber. Conclusion: So, low dietary fiber consumption maybe a possible causal factor of raised CRP. Type 2 diabetic patients who took less dietary fiber in their diets had elevated blood CRP levels. DOI: http://dx.doi.org/10.3329/bjms.v11i2.11434 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 117-120